Typhoid Vaccine in EPI; Relatively New Perhaps Overdue Strategy - Dhakal, Sanjaya; Dhakal, Ajaya Kumar (Journal of Nepal Paediatric Society, 2013)
Theoretically, it is possible to eliminate Salmonella, pathogenic bacteria that can cause a potentially fatal enteric fever. However, given the high prevalence of the disease in low-income countries that lack adequate facilities for sewage disposal and water treatment, and the fact that people can be long-term asymptomatic carriers, this goal is currently unrealistic. This levies constant need of a preventive measure to reduce morbidity and mortality in children associated with Typhoid Fever in endemic countries like Nepal. Currently, the best possible approach is to integrate the Typhoid vaccination into the Expanded Program of Immunization (EPI) until an improved sanitation and sewage disposal system is attained. We must acknowledge that this approach is not definitive until sufficient political and economic attention is received from all stakeholders. DOI: http://dx.doi.org/10.3126/jnps.v33i2.8715 J Nepal Paediatr Soc. 2013; 33(2):152-154